2023
DOI: 10.3390/computers12050105
|View full text |Cite
|
Sign up to set email alerts
|

Detecting COVID-19 from Chest X-rays Using Convolutional Neural Network Ensembles

Tarik El Lel,
Mominul Ahsan,
Julfikar Haider

Abstract: Starting in late 2019, the coronavirus SARS-CoV-2 began spreading around the world and causing disruption in both daily life and healthcare systems. The disease is estimated to have caused more than 6 million deaths worldwide [WHO]. The pandemic and the global reaction to it severely affected the world economy, causing a significant increase in global inflation rates, unemployment, and the cost of energy commodities. To stop the spread of the virus and dampen its global effect, it is imperative to detect infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…However, this study observed three main challenges in previous research studies (Bhatt and Shah, 2023;El Lel et al, 2023;Mabrouk et al, 2022;Visuña et al, 2022;Win et al, 2021;Deb and Jha, 2020). The first challenge is the availability of diverse and sufficient data is crucial for the success of ensemble CNNs.…”
Section: Ensemble Cnns In Chest Disease Diagnosingmentioning
confidence: 91%
See 2 more Smart Citations
“…However, this study observed three main challenges in previous research studies (Bhatt and Shah, 2023;El Lel et al, 2023;Mabrouk et al, 2022;Visuña et al, 2022;Win et al, 2021;Deb and Jha, 2020). The first challenge is the availability of diverse and sufficient data is crucial for the success of ensemble CNNs.…”
Section: Ensemble Cnns In Chest Disease Diagnosingmentioning
confidence: 91%
“…In a similar El Lel et al (2023) proposed eleven ensemble CNNs (etc., random forest classifier, logistic regression, k-neighbors classifier, and majority voting) consisting of six CNNs and a classifier layer to classify the input image into COVID-19 or normal. Through rigorous evaluation, the logistic regression ensemble model emerged as the most effective in terms of COVID-19 detection accuracy, achieving an impressive accuracy rate of 96.29%.…”
Section: Ensemble Cnns In Chest Disease Diagnosingmentioning
confidence: 99%
See 1 more Smart Citation